Synthesis, characterization and antifungal activity of coated silver nanoparticles-nystatin and coated silver nanoparticles-clotrimazol - Anwar Adil Hameed; Mustafa Abdulghafoor Alheety (Tikrit Journal of Pure Science)
Two silver nanoparticles containing compounds were prepared by simple chemical reactions and characterized by X-ray diffraction (XRD), infra-red spectrum (FTIR) and atomic force microscope (AFM). These functionalized silver nanoparticles were used to study their biological activity against four types of fungi. These compounds proved to have high inhibition effect against all types of studied fungi. Due to the presence of silver nanoparticles which increases nystatin and clotrimazol interact with the fungi.